The Effectiveness Of The Flipped Classroom Method In Dokkai 3 Course To Improve The Reading Skills Of Students Of Japanese Language And Culture Studies Level II Darma Persada University - Zainur Fitri; Bertha Nursari; Metty Suwandany; Tia Martia (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
This study aims to determine the implementation of The Flipped Classroom Method in Dokkai 3 Course which focuses on reading comprehension skills in Japanese and the effectiveness of The Flipped Classroom Method in Dokkai 3 Course to improve students' reading comprehension skills in Japanese. The research design used was a quasi-experimental method with One Group Pre-Test and Post-Test Design. Participants in this study were second-level students in the 2019/2020 academic year of the Japanese Language and Culture Study Program, Faculty of Japanese Language and Culture, Darma Persada University, totaling 47 people, with details of male 28 students and 19 female students. The results showed that there was a significant difference between students' skills before and after using The Flipped Classroom Method in the Dokkai 3 Course. This can be seen from the score before being given The Flipped Classroom Method was 68, while the average reading comprehension skills after being given The Flipped Classroom Method was 71. This means that descriptively it is known that the reading comprehension skills of The Flipped Classroom Method was increased. In The T-Test, it can be seen that the Aysmp.Sig value obtained from the average value of personality ideas is 0.024 <0.05 at the 95% significance level. This showed that the reading comprehension skills between before and after being given The Flipped Classroom Method is significantly different or in other words The Flipped Classroom Method provides a significant increase in reading comprehension skills. Related to the results of the questionnaire, it was obtained that most of the respondents responded very positively to the implementation of The Flipped Classroom Method and agreed that The Flipped Classroom Method was in The Dokkai 3 Course. This was because they felt the many benefits derived from the application of that method.